Measuring university students' attitudes towards child labor - Hassan, Haider Fadhil (Al-Adab Journal, 2022)
Child labor is work that deprives a child of his childhood and negatively affects his life. It is a global phenomenon that appears in several countries. In Iraq, this phenomenon is widespread in all cities to a large extent. The current research aims to build a scale of university students’ attitudes towards child labor, measure these trends, and identify the differences in university students’ attitudes towards child labor according to the gender variable and the academic specialization variable. The research sample consisted of (100) male and female students from the scientific and humanitarian specialization. The researcher built a scale of university students' attitudes towards child labor. The results of the research showed that university students have negative attitudes towards child labor, and that there are no significant differences in university students’ attitudes towards child labor according to the gender variable. The results also showed the presence of statistically significant differences in the attitudes of university students towards child labor according to the non-scholastic specialization and in favor of students with a scientific specialization. The researcher reached a set of recommendations and suggestions in the light of the research results.